Catalytic oxidative cracking of n-propane over nanosized gold supported La2O3 catalysts. (1st December 2018) - Al-Sultan, Fawaz S.; Basahel, Sulaiman N.; Narasimharao, Katabathini
Graphical abstract: Highlights: Au-La2 O3 and Au-SO4 2− /La2 O3 catalysts were used for n -propane oxidative cracking. Au and SO4 2− loading have an effect on catalytic oxidative cracking activity. Au metal and partially oxidized Au species dispersed on support surface. Reducibility, acidity, surface area and Au particle size played an important role. 0.2Au-10SO4 2− /La2 O3 showed highest and stable activity for 20 h. Abstract: Nanosized gold deposited bare and sulfated La2 O3 samples were synthesized and utilized for catalytic oxidative cracking of n -propane. Bare La2 O3 showed only 10% conversion with 15% olefin selectivity, however significant enhancement in the conversion of n -propane was observed when La2 O3 support was deposited with 0.2 wt% gold (25% conversion and 39% olefin selectivity) at 550 °C. Further improvement in conversion (46%) and in 53% selectivity was observed with gold supported 10 wt% SO4 2− /La2 O3 catalyst. Gold supported sulfated La2 O3 catalyst showed stable activity even after 20 h and the catalysts are resilient to formation of the coke. Presence of partially oxidized gold species and sulfate ions resulted enhancement in Lewis and Brönsted acidity of the catalysts. Homogeneous dispersion of gold nanoparticles and presence of metal-sulfate interactive species was observed in case of gold supported sulfated La2 O3 catalyst as evidenced by TEM, CO chemisorption and H2 -TPR analyses. The enhancement of catalytic activity could be attributed to small particle size, balanced Lewis and Brönsted acid sites and high dispersion of gold nanoparticles, surface area and oxygen mobility of the catalysts.